Atrial Septal Defect with Normal Pulmonary Arterial Pressure in Adult Cyanotic Patient - Kim, In-Cheol (J Cardiovasc Ultrasound, 2014)
A 22-year-old male presented with recurrent stroke, central cyanosis, and dyspnea. Transesophageal echocardiography and cardiac catheterization revealed bidirectional shunt flow through atrial septal defect (ASD) without pulmonary arterial hypertension. The orifice of inferior vena cava facing towards ASD opening led partially right to left shunt resulting in cyanosis with normal pulmonary arterial pressure.